As perspectivas contemporâneas do direito internacional consuetudinário - Flávia Resende Ferreira e Melo (2022)
This study aims to analyze the contemporary perspectives of Customary International Law. The central question of this study is based on the construction of a post-modern doctrine of Customary International Law in order to respond to the modifications of the XXI century international society, remaining as an important source of International Law. For this purpose, the research begins with a historical-legal investigation, contextualizing the understanding of the customary norms since the medieval period until the present time. Considering the historical analysis, it is ascertained that the international custom has always been used as a way to legitimize the domination and the interests of the more developed countries in the international society. Furthermore, it is aimed to examine, through a comparative-legal investigation, the role of the International Court of Justice, international criminal courts, arbitral tribunals and domestic courts in relation to the identification and development of the customary norms. The contemporary approaches of these norms englobe the evaluation of the interrelationship between the constitutive elements of state practice and opinio juris and the contribution of the third world countries to the establishment of more inclusive norms in the international legal order. Moreover, it is intended to identify, through a descriptive-legal investigation, the challenges of Customary International Law in the context of the New International Order marked by the globalization and a greater interstate cooperation, besides the increased participation of other actors, such as international organizations, nongovernamental organizations, individuals, non-state armed groups and transnational corporations. In the end, a construction of a post-modern doctrine is identified based on the deliberative reasons of state and non-state actors, on the opinio juris communis, considering the common interests of humankind, on the resolutions of the international organizations and the participation of the international civil society. Therefore, this work has an objective purpose to outline the main jurisprudential and doctrinal contributions to the establishment of customary norms that reflect a more extensive participation of the contemporary international society.